Sarah Kubitschek Hospital - Rio De Janeiro: a study on ventilation and air renewal - Cestavo, Rebeca Longatti; Meirelles, Célia Regina Moretti; Nazareth, Samuel Bertrand Melo (Seven Editora, 2023)
The relationship between architecture and air quality is observed in different moments in history and was evidenced during the pandemic of COVID-19, since there is a direct relationship between the building, the openings, air renewal and how these factors affect the user’s health. In this sense, this work aims to analyze ventilation systems in hospital areas, especially infirmaries, places susceptible to contamination by airway infections. The methodological procedures start from a literature review and have as a case study the infirmary of the Sarah Kubitschek Hospital in Rio de Janeiro, with the analysis carried out through computer simulations. The research demonstrated the importance of different types of ventilation in different spaces within a hospital, as well as the need for air renewal as a promoter of the environment’s salubrity, and patients’ well-being, a strategy applied by João Filgueiras Lima in this hospital. The analyses show that such strategies contribute to maximize natural ventilation promoting greater natural air renewal and user comfort. DOI: https://doi.org/10.56238/colleinternhealthscienv1-078